What is christianity? - Harnack, Adolf von (New York Harper & Row, 1957)
Harnack's work is considered by many experts in the field of theology to be unsurpassed. His approach is not meant to prove any set of dogmatic beliefs, as many Christian scholars set out to do, but is one of objectivity. His factual approach is not col
Keywords: Christianity -- Essence, genius, nature